The Effectiveness of Topical Tea Tree Oil (Terpinen-4-Ol) in Human Demodicosis: A Literature Review - Ayu Mayangsari; Ratih Pramuningtyas; Aulia Nissa Rizky Hariyono; Zhela Fatin Fatiha; Tia Mella Citra (Budapest International Research and Critics University, 2021)
Demodecosis is a skin disorder caused by parasites with the demodicosis type. The primary cause of this condition in humans is two kinds of Demodex mites, D.folliculorum and D.brevis. Demodicosis are usually treated with TTO, but the effectiveness is not well documented. To evaluate the effects of topical Tea Tree Oil on demodicosis infestation in people. We use the following string in Google Scholar; PubMed; Science Directs with keywords (“Demodicosis”iORi“demodex”iOR